Breastfeeding position and attachment practices among lactating mothers: An urban community-based cross-sectional study from Vadodara city in western India - Kajal Davra; Paragkumar Chavda; Chandresh Pandya; Divya Dave; Kedar Mehta (Elsevier, 2022)
Problem considered: Incorrect breastfeeding technique is a common cause of breastfeeding problems and subsequent discontinuation. Representative community-based data on practice of correct breastfeeding technique is not easily available. This study assessed the breastfeeding techniques as practiced by mothers having child under 6 months of age residing in urban slum areas of a city in western India. Methods: This community-based cross-sectional study was conducted after ethics committee approval. We selected 210 mothers through population proportionate to size cluster sampling with 30 slum areas as clusters and 7 mothers from each cluster. Breastfeeding technique was observed by a trained female investigator through a checklist based on Integrated Management of Neonatal and Childhood Illness guidelines. Outcome variables were percentage of mothers with good position, good attachment and effective suckling. EpiData analysis and MedCalc were used for data analysis. Results: The proportion (95% confidence interval) of mothers having correct breastfeeding position was 45.2% (35.2-55.3%), good attachment 73.8% (67.2-80.4%) and effective suckling 73.3% (67.8-78.8%). 128 (61%) mothers reported having been taught the technique of breastfeeding by someone, the most common source being nurse at health facility. Nuclear family, low parity and previous training in breastfeeding technique were positively associated with correct breastfeeding technique. Conclusion: The proportion of mothers with correct breastfeeding technique was low in light of the robust presence of maternal and child health programs.